HYDROGEL: RESPONSIVE STRUCTURES FOR DRUG DELIVERY - P. N., MALLIKARJUN; S., ANUSHA; V., SAI NANDINI; B., RAMA RAO; P. V., KAMALA KUMARI; Y., SRINIVASA RAO (International Journal of Applied Pharmaceutics, 2021)
Hydrogels are water-swollen 3D networks made of polymers, proteins, small molecules, or colloids. They are porous in structure and entrap/encapsulate large amounts of therapeutic agents and biopharmaceuticals. Their unique properties like biocompatibility, biodegradability, sensitivity to various stimuli, and the ability to be easily conjugated with hydrophilic and hydrophobic drugs with a controlled-release profile make hydrogels a smart drug delivery system. Smart hydrogel systems with various chemically and structurally responsive moieties exhibit responsiveness to external stimuli including temperature, pH, ionic concentration, light, magnetic fields, electrical fields, and chemical and biological stimuli with selected triggers includes polymers with multiple responsive properties have also been developed elegantly combining two or more stimuli-responsive mechanisms. This article emphasized the types, features, and various stimuli systems that produce responsive delivery of drugs.